HUBUNGAN ANTARA KECERDASAN EMOSI DENGAN KONTROL DIRI PADA ANGGOTA DIT SAMAPTA POLDA JATENG KALISARI SEMARANG - Alice Zellawati; Siraj Bugar Adhetian; Brigitan Argasiam (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas AKI Semarang, 2021)
This research aims to determine the relationship between emotional intelligence and self-control felt by members of the Dit Samapta Polda Tengah Jateng Kalisari Semarang. The population in this study were members of the Dit Samapta Polda Kalisari Semarang, Central Java, totaling 140 people. The number of samples used in this research was 120 people. The sampling technique used is incidental sampling. This research uses a psychological scale data collection method in the form of a Likert scale which consists of two scales, namely, an emotional intelligence scale of 40 items (? = 0.907) and a self-control scale of 10 items (? = 0.887). Based on the hypothesis proposed in this research, namely: